Aplicación de un sistema de costos por servicios en la empresa de capacitación y asesoramiento 3cgreat Solutions s.a.s., ubicada en la ciudad de Latacunga, periodo enero-marzo-2022 - Fogacho Criollo, Vanesa Johanna (2022)
The need for business today, is mainly to meet the needs and desires of customers, most entrepreneurs, mainly small businesses, define their prices of products or services offered according to the market, ie considering their competitors and empirically, without knowing if they generate a positive profit margin, which allows to cover the costs incurred, here is the importance of having a cost system that allows making the best decisions. Therefore, the purpose of this research was to design a cost system by service orders in the company 3C Great Solutions S.A.S., which allows the identification of the cost elements incurred during the different activities of the service, allowing to know the real costs. For the realization of the project, a research design was used that allowed the collection of information in the organization, and the bibliographic compilation, the techniques used were the interview and the observation sheet that was applied to the Manager and Accountant of the company, in order to obtain necessary and important information for the development of the project. The proposed cost system is designed in spreadsheets, which allow the manipulation of the different modules related to the resources that are part of the three elements of the cost, feeding the necessary information to determine the real cost of the training and the final accumulated cost of the service provided.